The use of Social Networking Sites (SNS) and quality of work life / Aida Shekh Omar, Wan Edura Wan Rashid and Afiza Abdul Majid - Shekh Omar, Aida; Wan Rashid, Wan Edura; Abdul Majid, Afiza (Research Management Institute, 2014)
One of the fastest growing Internet uses today is the social networking site (SNS). It is a populär platform where all the registered users share information with other registered users (Trusov, Bodapati & Bucklin, 2010). This popularity is mainly given by the fact that SNSs help to connect a person with other online users (e.g. friends, family members, colleagues), share information (e.g. blogs, photos, Videos), and help individuals and organizations with other purposes (e.g. promoting new products, recruiting new members).